2019
DOI: 10.1371/journal.pone.0210506
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with obstetric care in a population of low-educated native Dutch and non-western minority women. Focus group research

Abstract: BackgroundLow-educated native Dutch and non-western minority women have inadequate access to obstetric care. Moreover, the care they receive lacks responsiveness to their needs and cultural competences. Gaining a deeper understanding of their experiences and satisfaction with antenatal, birthing and maternity care will help to adjust healthcare responsiveness to meet their needs during pregnancy, childbirth and the postpartum period.MethodsWe combined the World Health Organization conceptual framework of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
1
25
0
4
Order By: Relevance
“…Care during pregnancy was the time period with highest proportion of dissatisfaction in our study. Contrary to this, a Dutch study showed that non-Western migrants were most satisfied with the antenatal care, 38 while a British study found little difference in satisfaction between the three periods. 34 These differences might be explained by different ways of organising the maternity care between countries, for instance, a more non-intervening approach to perinatal care, continuity of care and more home births in the Netherlands compared with Norway.…”
Section: Open Accessmentioning
confidence: 79%
“…Care during pregnancy was the time period with highest proportion of dissatisfaction in our study. Contrary to this, a Dutch study showed that non-Western migrants were most satisfied with the antenatal care, 38 while a British study found little difference in satisfaction between the three periods. 34 These differences might be explained by different ways of organising the maternity care between countries, for instance, a more non-intervening approach to perinatal care, continuity of care and more home births in the Netherlands compared with Norway.…”
Section: Open Accessmentioning
confidence: 79%
“…The availability and communication of information and personal control during pregnancy and childbirth is important for patient satisfaction among all pregnant women [ 20 , 21 ]. This satisfaction is thought to have both short-term and long-term effects on women’s health and the relationship with the infant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics and other ethnicities may have shown unfavorable attitudes due to larger representation of immigrants within those groups. For example, immigrants in the Netherlands reported issues of communication, autonomy and respect [ 18 ]. An Australian sponsored study looked at five host countries with significant immigrant populations and also found issues with communication and discrimination [ 19 ].…”
Section: Discussionmentioning
confidence: 99%